2011
DOI: 10.1089/jpm.2011.0187
|View full text |Cite
|
Sign up to set email alerts
|

High Scores on the Edmonton Symptom Assessment Scale Identify Patients with Self-Defined High Symptom Burden

Abstract: The terms symptom burden and symptom distress are frequently seen in palliative care literature yet are used in multiple ways ranging from addition of symptom scores to more in-depth assessments of interference in function. Patient input to date has had little role in these varied definitions yet previous reviews have suggested the importance of such input. This mixed qualitative and quantitative prospective study was conducted to seek patient input into the definition of 'symptom burden' and to correlate burd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 33 publications
0
27
0
1
Order By: Relevance
“…Policy development of this nature is occurring against a backdrop of global ageing, a rising prevalence of frailty and co-morbidity in chronic illness [3]. Meeting the palliative needs of such diverse populations is challenging and is made more difficult with growing evidence that patients face significant physical and psychological burden [4]. Elevated prevalence of psychological and physical burdens towards the end of life have been noted in patients with cancer [5], chronic kidney disease [6], COPD [7] and heart failure [8].…”
Section: Introductionmentioning
confidence: 99%
“…Policy development of this nature is occurring against a backdrop of global ageing, a rising prevalence of frailty and co-morbidity in chronic illness [3]. Meeting the palliative needs of such diverse populations is challenging and is made more difficult with growing evidence that patients face significant physical and psychological burden [4]. Elevated prevalence of psychological and physical burdens towards the end of life have been noted in patients with cancer [5], chronic kidney disease [6], COPD [7] and heart failure [8].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies found no significant correlation between symptom burden and PS of advance cancer patients 32,33 . Fu et al studied the relationship between symptom burden (using the ESAS) and the functional status (using the Functional Independence Measure [FIM]) of cancer patients in a rehabilitation unit 32 .…”
Section: Esas Itemmentioning
confidence: 86%
“…The average PPS score in their study was much higher than that in our study (69 vs. 36, respectively). They found no significant relationship between symptom burden and PS 33 . The latter two studies included patients with less symptom burden and better PS compared to our study.…”
Section: Esas Itemmentioning
confidence: 92%
See 1 more Smart Citation
“…They did not, however, consider other possible explanations for these high ratings, such as expected changes associated with advancing disease or patient preferences. In some cases, patients may rate their symptoms high, yet also view this as being a preferred or acceptable level of symptom control [25]. Attitudinal issues included viewing routine assessments as "unnatural" or burdensome for patients [15,28], or preferences to use one's own symptom assessments [29].…”
Section: Discussionmentioning
confidence: 99%